Optimalisasi Akuntansi Keuangan Untuk Masjid: Pendampingan Di Padukuhan Sonopakis Lor, Kasihan, Bantul, Yogyakarta - Wuku Astuti; Nisfatul Izzah; Dinda Dupalantu (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Transparent and accountable financial management is a pressing need for non-profit organizations, including mosques, to enhance the trust of congregants and donors. Unfortunately, many mosques in Indonesia lack adequate financial reporting systems due to limited human resources and accounting knowledge. This community service program aimed to enhance the capacity of mosque administrators in Padukuhan Sonopakis Lor, Kasihan Subdistrict, Bantul Regency, in preparing financial reports that comply with ISAK 35 standards. The methods used included lectures, training, mentoring, and hands-on practice in financial report preparation. The results showed that most mosque administrators successfully understood basic accounting principles, recorded transactions, and prepared financial reports, despite challenges such as limited competencies and initial resistance from mosque administrators. Through persuasive approaches and intensive training, the resulting financial reports met the transparency and accountability standards of ISAK 35. Ongoing mentoring is recommended to ensure the sustainability of this practice, serving as a model of best practices for other mosques.